Exosome-mediated therapeutic delivery: a new horizon for human neurodegenerative disorders’ treatment (with a focus on siRNA delivery improvement) - Seyfizadeh, Nayer; Seyfizadeh, Narges (Process biochemistry, 2019)
Neurodegenerative disorders are one of the leading causes of death and disability worldwide, which also poses major burden on health care systems. siRNA opens a new perspective to treat diseases pertaining to gene functions by silencing its targeted mechanisms. Exosome-mediated siRNA is a newly developed unique approach in order to improve the efficiency of siRNA delivery system. This method is potentially a convenient scheme for CNS disorders, because of its therapeutic based delivery mechanistic approach across the blood-brain barrier (BBB). Exosomes are extracellular nanostructures that could carry a variety of cargoes and performs many different functions based on their origin. Exosomes. In this review, we mainly focus on the third application and discuss exosome biogenesis and its therapeutic applications in neurodegenerative disorders. We summarize the latest studies on how exosome improves small RNA therapy and give an overview of exosome cargo loading techniques, its source cell selection, and efficient delivery routes.